A Simple Cultivation Method for Chesapeake Bay Ulva intestinalis for Algal Seed Stock. (21st March 2014) - Li, Ji; Kangas, Patrick; Terlizzi, Daniel E.
Abstract: Ulva spp. are valuable economically as edible green algae, and they also have environmental value in biofiltration. Cultivation of Ulva spp., in fact macroalgal cultivation generally, is limited in the USA. As part of a larger effort to develop macroalgal cultivation in the Chesapeake Bay for nutrient remediation, we developed a "seeding" method for Chesapeake Bay isolates of U. intestinalis . Ulva intestinalis thalli were induced to produce and release free‐swimming zoospores by desiccation and rehydration. The zoospores then were induced to settle on the nylon nets by dark incubation. Rhizoids from the zoospores formed on the nets, and the nets became covered with green filaments which developed tubular thalli. Nets with thalli can be incubated in indoors or deployed in natural water to generate production‐scale cultivation of U. intestinalis in the Chesapeake Bay. Such cultivation can be integrated with the growing oyster aquaculture industry in the Chesapeake Bay area, U. intestinalis serving as biofilters to remove oyster wastes and increase economic benefit through water quality enhancement and nutrient credits, and as an aquaculture product in their own right.